The influence of citrate and oxalate on 99TcVII, Cs, NpV and UVI sorption to a Savannah River Site soil. (June 2017) - Montgomery, D.; Barber, K.; Edayilam, N.; Oqujiuba, K.; Young, S.; Biotidara, T.; Gathers, A.; Danjaji, M.; Tharayil, N.; Martinez, N.; Powell, B.
Abstract: Batch sorption experiments were conducted with 0.5–50 ppb 99 Tc, 133 Cs, 237 Np and U in the presence and absence of citrate and/or oxalate in a 25 g/L Savannah River Site (SRS) soil suspension. Citrate and oxalate were the ligands of choice due to their relevancy to plant exudates, the nuclides were selected for their wide range of biogeochemical behavior, and the soil from SRS was selected as a model Department of Energy (DOE) site soil. Batch samples were continually mixed on a rotary shaker and maintained at a pH of approximately 5. Analysis via ICP-MS indicated that sorption of 237 Np increased with ligand concentration compared to baseline studies, as did sorption of 99 Tc although to a lesser extent. The increased sorption of 237 Np is proposed to be due to a combination of factors that are dependent on the ligand(s) present in the specific system including, ligand dissolution of the soil by citrate and formation of tertiary soil-oxalate-Np complexes. The increased 99 Tc sorption is attributed to the dissolution of the soil by the ligands, leading to an increase in the number of available sorption sites for 99 Tc. Uranium sorption decreased and dissolution of native uranium was also observed with increasing ligand concentration, thought to be a result of the formation of strong U-ligand complexes remaining in the aqueous phase. The majority of these effects were observed at the highest ligand concentrations of 50 mgC /L. No notable changes were observed for the 133 Cs system which is ascribed to the minimal interaction of Cs + with these organic ligands. Highlights: Citrate and/or oxalate amended and baseline batch sorption studies performed on SRS soil with 133 Cs, 99 Tc, 237 Np and U. Increased sorption observed for 99 Tc and 237 Np in presence of high concentrations of amendments. Decreased sorption and dissolution of native uranium observed in presence of amendments. Little to no effect on Cs sorption in the presence of amendments. Ligand dissolution of the clay fraction of the soil observed at high ligand concentrations.